Başbakanlık Devlet Arşivleri Osmanlı Arşivi’ndeki nümismatik ile ilgili belgeler kataloğu : Darphaneler, ilgili kuruluşlar, madenler, meskûkât, kaime, madalya, nişanlar vb. = Documents of numismatic importance in the Ottoman Archives : coinage-medals and orders-mints and their administration-mint masters and superintendents-stampers of imperial monograms(Tuğra)-counterfeiters etc. - Ender, Celil. (İstanbul)
208 s.